Preparação, caracterização e estudo do comportamento térmico dos selenatos duplos de cálcio, de berílio e de amônio - Costalonga, Ademir Geraldo Cavalari [UNESP]; Spirandeli Crespi, Marisa [UNESP]; Ribeiro, Clóvis Augusto [UNESP] (My University, 1996)
The preparation and thermal decomposition of ammonium selenate and calcium and beryllium selenates have been reported previously. However, there are not any information in the literature concerning the thermal decomposition of double selenates of calcium, of beryllium and ammonium. Thermogravimetry (TG), Differential Thermal Analysis (DTA) were used in the studies and characterisation of these compounds.
Preparation, characterization and thermal behavior of double selenates of calcium, beryllium and ammonium
Keywords: Ammonium selenate; Beryllium; Calcium; Differential thermal analysis; Double selenates; Thermogravimetry